Hypolipidemic effect of sitagliptin, voglibose and glimepiride in combination with metformin in patients with type 2 diabetes mellitus at a tertiary care teaching hospital: a comparative study - Kala, P.; Rani, R. Jamuna (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The prevalence of coronary artery disease has been increased in diabetic dyslipidemia; hence the present study would like to compare the dyslipidemic effects of Sitagliptin, Voglibose, and Glimepiride in combination with Metformin in type 2 diabetes mellitus patients. Methods: This study was a Prospective, Randomized Clinical trial conducted at SRM medical College Hospital and Research centre. Potheri, Kancheepuram District in diabetic outpatient department after obtaining approval from Institutional Ethics Committee. The patients receiving antidiabetic drugs were divided into three groups. Patients received Metformin with Sitagliptin were grouped as I, Metformin with Voglibose were named as Group II and Metformin with Glimepiride were marked as Group III. Based on the inclusion and exclusion criteria, in each group, 40 patients were assigned as per simple randomization method. The level of lipid profile and BMI was evaluated at the end of 6 months. Results: There was a significant reduction of Total Cholesterol (TC) in Group II and Group III (p value- <0.001, <0.006). Group I showed significant elevation of HDL-C level with the p value of <0.03. Group III showed significant reduction of Triglyceride (TG) level with the p value of <0.04, significant reduction of Low Density Lipoprotein Cholesterol (LDL-C) level with the p value of <0.02 and significant reduction in Very Low Density Lipoprotein Cholesterol (VLDL-C) level with the p value of <0.05. There was no significant reduction in Body Mass Index (BMI) among the groups. On multiple comparisons, Group III showed higher efficacy in reducing TC, TG, LDL-C and VLDL-C levels. Conclusions: The results of this study were analysed and it could be concluded as Metformin with Glimepiride combination (Group III) showed significant reduction of TC, TG, LDL-C and VLDL-C levels.